PENGARUH GAYA KEPEMIMPINAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) DI POLITEKNIK LP3I JAKARTA KAMPUS JAKARTA UTARA - Iis Kartini (JURNAL LENTERA BISNIS, 2017)
This study entitled "The Effect of Leadership Style of Organizational Citizenship Behavior (OCB) In LP3I Polytechnic Campus Jakarta North Jakarta". The purpose of this study was to determine the influence of leadership style on organizational citizenship behavior at Polytechnic LP3I Jakarta, North Jakarta Campus and determined the dominant leadership style indicators affect the organizational Citizenship Behavior (OCB) at Polytechnic LP3I North Jakarta Campus conducted in this experiment, namely descriptive quantitative research methods. The population of this research is all employees of Polytechnic LP3I North Jakarta Campus that counted of 33 empolyees and sampling technique used is by simple random sampling which resulted in a sample of 33 employees. The instrument used in this study was a questionnaire and analysis of the data used is simple regression. The results of this research that there is a positive and significant effect of leadership style on organizational citizenship behavior amounted to 24.4%. There is a positive correlation between leadership style to organizational citizenship behavior demonstrated by the correlation coefficient (R) of 0.494 (very high).Keyword: PENGARUH, GAYA KEPEMIMPINAN, ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB)